NEW DIRECTIONS FOR RESEARCH AND PEDAGOGY IN BOOK HISTORY - HOWSAM, LESLIE (Knygotyra, 2013)
This article addresses contemporary trends in the history of the book, focusing on both research and teaching. Given the great complexity of the interdisciplinary study of book science (called ‘book history’ or ‘the history of the book’ in North America and Britain, and l’histoire du livre in France), students may be confused or overwhelmed when the subject is introduced. They may legitimately ask what they can expect to learn, and how the subject will be organized. This is especially relevant because their generation has grown up with computers and with digital texts, and also with a cultural discourse of globalization. The article considers the challenges of teaching and learning the history of the book from two points of view, both of which have produced rich results in research over the past twenty to thirty years. The first identifies each individual book as a means of communication and cultural transfer; the second incorporates “the book” as a conceptual category in larger historical narratives working from the perspectives of time and space. While both perspectives can be of value for an introduction to this protean subject, neither offers a fully satisfactory response to the challenge of producing a coherent narrative. There is a discussion of transnational approaches to the history of the book; these are compared favourably to the more limited national approach, but the scholarly impulse to undertake the latter is contextualized. The article concludes with a discussion of Digital Humanities and demonstrates how this new field of study can work collaboratively with scholars in book history.
Keywords: book science; book history; communication; literature; pedagogy; nation; transnational; digital humanities